Action priorities to facilitate planning of the transition to adulthood of young people with profound intellectual disability. - Gauthier-Boudreault, Camille; Gallagher, Frances; Couture, Melanie (International Journal of Developmental Disabilities, 2026)
Objectives: It is essential for parents and professionals to be engaged in identifying and developing solutions that facilitate the transition to adulthood of young people with profound intellectual disability. However, most of them are dissatisfied in various ways with the current services available. To date, there is a paucity of literature guiding the development of solutions to meet the needs of young people with profound intellectual disability, their parents and their professionals. This study aimed to understand actions priorities to facilitate transition planning for young people with profound intellectual disability according to parents and professionals. Methods: Parents and professionals from the education, health and community sectors participated in a three-stage prioritization process. Results: The multistage methodological process for obtaining the viewpoints of parents and professionals involved in the planning of the transition to adulthood appear to be a relevant and realistic method. Both parents and professionals prioritized solutions in the informational and material support categories. They identified the creation of a transition guide and support for the development of meaningful activities for individuals with profound intellectual disability as the most feasible and important solutions. Both also highlighted the need to increase the number of places in day activity centres and to have a one-stop-shop for both information and guidance from a single actor during transition process. Conclusions: Parents and professionals had similar action priorities, which pointed to the most interesting ways forward to develop in future studies of the transition to adulthood of young people with profound intellectual disability.